Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fimmu.2022.831844
|View full text |Cite
|
Sign up to set email alerts
|

High Salt Induces a Delayed Activation of Human Neutrophils

Abstract: High salt (NaCl) concentrations are found in a number of tissues under physiological and pathological conditions. Here, we analyzed the effects induced by high salt on the function of human neutrophils. The culture of neutrophils in medium supplemented with high salt (50 mM NaCl) for short periods (30-120 min) inhibited the ability of conventional agonists to induce the production of IL-8 and the activation of respiratory burst. By contrast, exposure to high salt for longer periods (6-18 h) resulted in the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
2
5
0
Order By: Relevance
“…In our settings, neutrophils were simultaneously activated by PMA/Pyocyanin and treated with high salt; these conditions augmented ROS production in high hypertonicity. This is in line with recent findings where NaCl initially inhibits (up to 2 hours) ( 18 , 40 ) but later (6 to 18 hours) fosters ROS production ( 18 ), even at lower osmolarities (190 - 200 mM). Our higher salinity was enough to induce oxidative stress in short-term cell cultures.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our settings, neutrophils were simultaneously activated by PMA/Pyocyanin and treated with high salt; these conditions augmented ROS production in high hypertonicity. This is in line with recent findings where NaCl initially inhibits (up to 2 hours) ( 18 , 40 ) but later (6 to 18 hours) fosters ROS production ( 18 ), even at lower osmolarities (190 - 200 mM). Our higher salinity was enough to induce oxidative stress in short-term cell cultures.…”
Section: Discussionsupporting
confidence: 93%
“…The latest publication showed that the effect of additional 50 mM NaCl was time-dependent and caused a delayed activation of human neutrophils. In short-term and long-term neutrophil cultures, production of IL-8 and respiratory burst were inhibited or augmented, respectively ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent study by Hishida et al demonstrated that IL-1ß deficiency attenuated the methylglyoxal-induced PF [ 28 ]. Similarly to our results, Mazzitelli et al found that while high-salt environment leads to the activation of neutrophils, osmotic control mannitol had no effect [ 29 ]. This phenomenon may be because immune cells express a high number of sodium transport proteins that can activate inflammatory pathways in lymphocytes independently from osmotic stress [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, a recent study by M azzitelli et al . [ 34 ] found the opposite, concluding that high salt concentration, rather than osmolarity, led to activation of the neutrophil response. Regardless of the mechanism, it can be speculated that ATP hydrolysis in ciliated epithelial cells may also be affected by HS and reduce CBF.…”
Section: Discussionmentioning
confidence: 99%